Molecular Interactions From the Density Functional Theory for Chemical Reactivity: The Interaction Energy Between Two-Reagents - Miranda-Quintana, Ramón Alain; Heidar-Zadeh, Farnaz; Fias, Stijn; Chapman, Allison E. A.; Liu, Shubin; Morell, Christophe; Gómez, Tatiana; Cárdenas, Carlos; Ayers, Paul W. (Frontiers in Chemistry, 2022)
Reactivity descriptors indicate where a reagent is most reactive and how it is most likely to react. However, a reaction will only occur when the reagent encounters a suitable reaction partner. Determining whether a pair of reagents is well-matched requires developing reactivity rules that depend on both reagents. This can be achieved using the expression for the minimum-interaction-energy obtained from the density functional reactivity theory. Different terms in this expression will be dominant in different circumstances; depending on which terms control the reactivity, different reactivity indicators will be preferred.